2021
DOI: 10.1007/s40617-020-00530-y
|View full text |Cite
|
Sign up to set email alerts
|

Restructuring Law Enforcement Agencies to Support Prosocial Values: A Behavior-Scientific Model for Addressing Police Brutality

Abstract: Policing in the United States is irrefutably a component of systemic racism. The history of police brutality against the Black community can be found in our amendments, laws, and cultural practices-it is an infrastructure of oppression. Though police brutality is not a new development, it has reached a fever pitch with the deaths of George Floyd and Breonna Taylor. Recent calls to defund the police puts law enforcement agencies squarely, and rightly, in the spotlight of social justice movements and reform. Cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 38 publications
0
2
0
5
Order By: Relevance
“…Research suggests that law enforcement trainings can reinforce stereotypes. Ghezzi et al (2021) illustrated that implicit bias training that does not focus on changing behavior, or enacting new behavior, is not successful in shifting conduct in the long term. Sim et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research suggests that law enforcement trainings can reinforce stereotypes. Ghezzi et al (2021) illustrated that implicit bias training that does not focus on changing behavior, or enacting new behavior, is not successful in shifting conduct in the long term. Sim et al.…”
Section: Discussionmentioning
confidence: 99%
“…Police trainings utilizing a DisCrit lens Research suggests that law enforcement trainings can reinforce stereotypes. Ghezzi et al (2021) illustrated that implicit bias training that does not focus on changing behavior, or enacting new behavior, is not successful in shifting conduct in the long term. Sim et al (2013) found that trainings can be presented in such a way that heightens bias among law enforcement who participate (Sim et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…A literatura traz propostas de intervenção para o racismo presente em algumas instituições, como por exemplo: escolas (Orlandi & Reis, 2022), universidades (Najdowski et al 2021), delegacias de polícia (Parks & Kirby, 2022;Ghezzi et al, 2022) e unidades de saúde que oferecem serviços em Análise do Comportamento Aplicada -Applied Behavior Analysis (ABA), em inglês (Čolić et al, 2022). Orlandi e Reis (2022), por exemplo, apresentam uma proposta de intervenção no nível cultural para enfrentar o racismo no contexto religioso nas escolas.…”
Section: Intervenções Para Racismo Institucionalunclassified
“…No contexto policial, Ghezzi et al (2022) apresentam uma proposta para intervenção no racismo individual com agentes que atuam na aplicação da lei, baseada no Treino de Aceitação e Compromisso (Acceptance and Commitment Training 9 -ACT, em inglês). Os autores partem da premissa que os policiais enfrentam diariamente alta carga de estresse, pressão por resultados e exposição a práticas institucionais racistas.…”
Section: Intervenções Para O Racismo Individualunclassified
See 1 more Smart Citation